Zakat Fundraising in Indonesia: Continuity, Legal Framework, and Digital Transformation - Khoiriyah, Faya Rizti; M. Fahmi Hidayat (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2025)
This study examines continuity and change in zakat fundraising in Indonesia, tracing its evolution from community-based traditional channels to formal institutions and digital platforms. Using a Systematic Literature Review (SLR) guided by the PRISMA framework, 67 peer-reviewed articles published between 2015 and 2025 were analyzed. The findings show that zakat fundraising in Indonesia follows a layered and hybrid trajectory rather than a linear shift from tradition to digitalization. Traditional mechanisms rooted in religious authority, communal trust, and local culture remain influential alongside institutional and digital channels. While institutionalization under Law No. 23 of 2011 has strengthened governance and accountability, tensions persist between state-based and civil society organizations. Digitalization enhances efficiency and outreach, yet trust, digital literacy, religious perceptions, and data security limit adoption. A hybrid model is essential for sustainable zakat fundraising in the digital era. Keywords: zakat fundraising; digitalization; institutionalization; Islamic philanthropy; Indonesia   Abstrak Penelitian ini menelaah keberlanjutan dan perubahan praktik penggalangan zakat di Indonesia, dari cara tradisional berbasis masyarakat hingga lembaga formal dan platform digital. Menggunakan Systematic Literature Review (SLR) dengan kerangka PRISMA, penelitian ini menganalisis 67 artikel peer-reviewed yang terbit antara 2015 dan 2025. Hasilnya menunjukkan bahwa penggalangan zakat berjalan secara bertingkat dan hybrid, bukan sekedar berpindah dari tradisional ke digital. Mekanisme tradisional yang berakar pada otoritas agama, kepercayaan masyarakat, dan budaya lokal tetap berperan di samping cara formal dan digital. Institusionalisasi berdasarkan Undang-Undang No. 23 Tahun 2011 memperkuat tata kelola, namun ketegangan antara organisasi zakat berbasis negara dan masyarakat sipil tetap ada. Digitalisasi meningkatkan efisiensi dan jangkauan, tetapi adopsinya masih terbatas karena kepercayaan, literasi digital, persepsi agama, dan keamanan data. Model hybrid dianggap penting untuk keberlanjutan penggalangan zakat di era digital. Kata Kunci: penggalangan zakat; digitalisasi; institusionalisasi; filantropi Islam; Indonesia